MEREFLEKSIKAN HUBUNGAN ANTARA ETIKA ARISTOTELIAN DAN BISNIS DENGAN STUDI KASUS LUMPUR LAPINDO - Agustinus W. Dewantara (Arete, 2013)
Oftentimes, the link between ethics and business escapes our notice. Business practices in Indonesia often wax corruptive and conspiring, with the misuse of representation and power, and rife with immorality. Yet, business is precisely often related to economic power and the ways of controlling it. Ethics allows the science of business to develop virtues through each action that involves the use of economic power. Truly ethical conduct is the dream of every man. That is why doing business should not be equated to "dirty play". Aristotle can become a reference point for the study of national ideals organized by a government that is just and good. The discussion of this topic takes the mudflow case of Lapindo in Sidoarjo as an example. We hope that this study could be a little contribution to the study of ethics in the national life of Indonesia and the social life of our people, two things that one feels is continually sinking into the mire as time passes